'OFF-to-ON' fluorogenic amino acids into small proteins - Reese, Abigail Eleanor (The University of Edinburgh, 2023)
Interleukin (IL)-33 is an IL-1 family cytokine, known as an alarmin, which is released from the respiratory epithelium during tissue injury caused by stimuli such as viruses, allergens, or cigarette smoke. Subsequently, IL-33 provokes a rapid type-2 immune response, promoting inflammation in a range of non-resolving inflammatory diseases, like asthma, atopic dermatitis, and rheumatoid arthritis. However, after IL-33 is released, little is known about the fate of the cytokine. Herein, we describe the introduction of a synthetic biology platform to detect and track the movements of IL-33 using fluorescent and environmentally sensitive fluorogenic dyes. Briefly, chemical aminoacylation was optimised to load a range of unnatural dyes onto a tRNA substrate. The tRNA was supplemented into an in vitro translation system to site-specifically encode the dyes into the protein’s sequence using amber suppression technology. A range of fluorescent and fluorogenic IL-33 mutants were produced to analyse the cytokine’s localisation and activity in real-time using fluorescence microscopy. In addition, an IL-33 biosensor was developed with a fluorogenic amino acid encoded directly into the binding site, displaying an increase in fluorescence upon IL-33 binding, which could be useful in disease diagnosis. Overall, this technology will provide us with a platform to visualise IL-33 and learn more about the nature of the cytokine in inflammation.
Keywords: Interleukin-33; IL-33; fluorescent fusion reporters; protein tagging; methodology